Mortality by suicide: a comparative study of Amapá with the Northern region of Brazil (2008-2017) - Arantes da Cunha, Arthur; Corona, Rodolfo Antonio; Steyse Rocha Aquino, Elizabete; Sena de Lucena, Larissa; Kazanowski, Juliana; de Lima Pinto, Wellington; Castilho Martins, Emerson Augusto (O Mundo da Saúde, 2022)
This study aimed to compare suicide mortality rates in the Northern region of Brazil and in Amapá, in addition to plotting temporal trends in mortality for the seven states and the region, during the period from 2008 to 2017. This is a retrospective time-series study (2008-2017). Suicide data recorded in the states of the Northern region were extracted from the Brazilian Public Security Yearbook. The source of population data, used for mortality calculations (×100,000), was the IBGE. To extract the trend of the series, simple temporal regressions were used. The SPSS 20.0 software was used. During the period examined 4,438 suicides were registered in the Northern region, of which 172 (3.88%) were in Amapá. There was no significant difference between the means of suicide mortality in Amapá (x=2.65±1.12) and that in the Northern region (x=2.66±0.72). However, it is necessary to consider the influence of underreporting in the time-series analysis of Amapá. The temporal regressions showed a significant upward trend in the suicide mortality rate in the Northern region (R2=0.566; p=0.012), in the state of Pará (R2=0.606; p<0.01), and in the state of Amazonas (R2=0.729; p<0.01). This growth may be, in part, related to socioeconomic factors, the increased vulnerability of population groups at risk and the improvement of health information services/systems that have taken place in recent years in Brazil. Thus, the results showed an increase in mortality from suicide in the Northern region and in two of its two most populous states. This indicates that prevention policies need to be strengthened, with special attention to the region’s most vulnerable populations, such as indigenous peoples.